Virtual education and the professional skills that firms demand - Quichiz-Chú, Alfredo (2021)
The environment faced by companies is characterized by its unpredictable and rapidly evolving nature. This environment, known as VUCA (volatility, uncertainty, complexity, and ambiguity), demands that companies hire the right professionals to help them achieve sustainable growth over time. This paper is a systematic review that aimsat finding if virtual education is aligned with the skills that firmscurrently demand on their staff, considering the recent pandemic and the VUCA environment. To this effect, a review of the 2015-2021 scientific literature of various databases and search engines has been pursued, placing an emphasis on the last two years (2020-2021). Following the methodology of a systematic review, inclusion and exclusion filters were applied to obtain only articles relevant to our research objective. The databases consulted for the Information search were Scopus, Scielo, Dialnet, Redalyc, CONCYTEC Virtual Library, as well as the Dimensions Index. We conclude that the training provided through virtual education is consistent with what current times demand, for it provides students with the skills they require (supply approach) and that companies need (demand approach). This consistency is further supported by a a favorable environment, put forth by things such as the familiarity of university faculty members with virtual environments, and new pedagogical methodologies to adequately transmit their knowledge and experiences. Regarding the determining factors of the effectiveness of virtual education, the different works consulted coincide in identifying three essential factors: ICT knowledge and digital skills; teaching quality, knowledge of the course and pedagogical techniques; and, the availability of technological infrastructure, especially the virtual one, and quality evaluation systems in courses and institutions.